2016
DOI: 10.1139/juvs-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Water resource management at catchment scales using lightweight UAVs: current capabilities and future perspectives

Abstract: Lightweight, portable unmanned aerial vehicles (UAVs) or ‘drones’ are set to become a key component of a water resource management (WRM) toolkit, but are currently not widely used in this context. In practical WRM there is a growing need for fine-scale responsive data, which cannot be delivered from satellites or aircraft in a cost-effective way. Such a capability is needed where water supplies are located in spatially heterogeneous dynamic catchments. In this review, we demonstrate the step change in hydrolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 96 publications
0
74
0
Order By: Relevance
“…Monitoring the flood flow, assessment of the flood inundation areas and related damages, post-flood landscape changes and pre-flood prediction are therefore urgently required. Among various scales of approaches for flood hazards (Sohn et al, 2008), the RPASs has been adopted for each purpose of the flood damage prevention and mitigation because it has the ability to take quick measurements at a low cost (DeBell et al, 2016;Nakamura et al, 2017). Figure 5 shows an example of the use of RPASs for prompt damage assessment by a severe flood occurred on early July 2017 in the northern Kyushu area, south-west Japan.…”
Section: Floodsmentioning
confidence: 99%
“…Monitoring the flood flow, assessment of the flood inundation areas and related damages, post-flood landscape changes and pre-flood prediction are therefore urgently required. Among various scales of approaches for flood hazards (Sohn et al, 2008), the RPASs has been adopted for each purpose of the flood damage prevention and mitigation because it has the ability to take quick measurements at a low cost (DeBell et al, 2016;Nakamura et al, 2017). Figure 5 shows an example of the use of RPASs for prompt damage assessment by a severe flood occurred on early July 2017 in the northern Kyushu area, south-west Japan.…”
Section: Floodsmentioning
confidence: 99%
“…This method offered a new range of application in many different research areas including forestry and agriculture (e.g., [1,2]), archeology (e.g., [3,4]) biology [5,6] and hydrology (e.g., [7,8]). An increase of studies using UAV photogrammetry is observed in geosciences, as well (e.g., [9,10]), where the DSMs and orthophotos are typically used for mapping and monitoring (e.g., [11,12]), object detection (e.g., [13]) or quantification of topographic changes, for instance (e.g., [14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…The attention of the most of operators is mainly focused on mini and micro UAS, because of their easiness of use and versatility. Over the last few years, small fixed-wing, helicopters, and multi-rotor Unmanned Aerial Vehicles (UAV), equipped with Global Navigation Satellite System and Inertial Navigation System (GNSS/INS), with a total weight of 5 kg or less (Micro-UAV [1]) are increasingly being used for different scientific environmental surveys [2][3][4], including Photogrammetry and Remote Sensing (RS) purposes [1].…”
Section: Introductionmentioning
confidence: 99%